2004
DOI: 10.3168/jds.s0022-0302(04)73191-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dry Cow Grouping Strategy and Prepartum Body Condition Score on Performance and Health of Transition Dairy Cows

Abstract: Multiparous Holstein cows (n = 337) on two commercial dairy farms were used to determine the effects of feeding a close-up diet for 21 (treatment S) or 60 d (treatment L). Milk yield was not affected by treatment; however, cows fed treatment S tended to have increased yields of fat, 3.5% fat-corrected milk, and protein during the first 5 mo of their subsequent lactation compared to treatment L. Cows fed treatment L gained more body condition score (BCS) during the dry period and had longer days to first servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 20 publications
(24 reference statements)
3
42
0
3
Order By: Relevance
“…This evaluation enables to maintain the herd's nutrition at the optimal level (Garnsworthy and Huggett, 1992). During the dry-up period, every farmer should care to keep BCS constant (Contreras et al, 2004).…”
mentioning
confidence: 99%
“…This evaluation enables to maintain the herd's nutrition at the optimal level (Garnsworthy and Huggett, 1992). During the dry-up period, every farmer should care to keep BCS constant (Contreras et al, 2004).…”
mentioning
confidence: 99%
“…It means that higher BCS before calving is associated with lower milk yield after calving. In the study of Contreras et al (2004) the group of cows with BCS 3.0 points and less had higher milk yield (+1.25kg) in the first five months of lactation than the group with BCS 3.25 points and more. Harris (2006) andDal Zotto et al (2007) also confirmed the negative relationship between BCS and milk protein production; the genetic correlation ranged from -0.03 to -0.22.…”
Section: Resultsmentioning
confidence: 99%
“…Περαι τέρω αΰξησή του δεν οδηγεί σε ανάλογη αύξηση της γαλακτοπαραγωγής, ενώ οι Waltner et al (1993) ανέ φεραν χαρακτηριστικά ότι αύξηση από τη βαθμίδα 4 στη βαθμίδα 5 σχετιζόταν με μείωση της γαλακτοπα ραγωγής. Οι Domecq et al (1997) και οι Contreras et al (2004) ανέφεραν σημαντική αύξηση της γαλακτο παραγωγής σε αγελάδες στις οποίες αυξήθηκαν τα ε πίπεδα του Δ.Θ.Κ. κατά τη διάρκεια της ξηράς περιό δου.…”
Section: επιδραση του δθκ στη γαλακτοπαραγωγηunclassified
“…Αντίθετα, θεωρείται αποδεκτό να ει σέρχονται οι αγελάδες στην ξηρά περίοδο στη βαθμί δα 2,75 έως 3 και να αυξάνουν τα σωματικά τους α ποθέματα κατά την περίοδο αυτή έως και 0,5 μονάδες του Δ.Θ.Κ. Πρόσφατα δημοσιευμένες μελέτες υπο στηρίζουν ότι μια τέτοια πρακτική μπορεί να έχει και ευεργετικά αποτελέσματα (Contreras et al 2004, Hoedemaker et al 2008). γ) Κατά τη διάρκεια των δυο πρώτων μηνών της γα λακτικής περιόδου είναι λογικό να υπάρχει μια κινη τοποίηση των σωματικών αποθεμάτων, η οποία όμως δε θα πρέπει να ξεπερνά τις 0,75 μονάδες του Δ.Θ.Κ.…”
Section: χρηση δθκ στη διαχειριση εκτροφων γαλακτοπαραγωγων αγελαδωνunclassified